Prospective, multicenter study to evaluate performance and safety of a re‐engineered temporary lead for InterStim™ therapy evaluation. Issue 8 (28th July 2022) - Elterman, Dean; Michaels, Jodi; Margolis, Eric; Harris‐Hicks, Janet; Burgess, Kimberly; Betts, Christopher; Harding, Christopher; Towers, Geoffrey; Hashim, Hashim; Ojo‐Carons, Akin; White, Amanda; Cannon‐Smith, Tracy; et al.
Abstract: Aims: The basic evaluation or percutaneous nerve evaluation (PNE) is a method to assess pre‐implantation therapeutic response in patients considering sacral neuromodulation for the treatment of refractory overactive bladder. A new PNE lead with a more robust design and greater distensibility designed to reduce the possibility of lead migration has recently been introduced to the market. The aim of this prospective, multicenter, global, postmarket study was to evaluate the clinical performance and safety of the new InterStim PNE lead with the foramen needle. Methods: Patients with overactive bladder were enrolled in this study. The primary objective of this study was to determine the proportion of subjects who demonstrated motor or sensory response(s) during lead placement using the InterStim PNE lead. Additional measures included the Patient Global Impression of Improvement (PGI‐I), patient satisfaction at the end of therapy evaluation, and change in bladder symptoms from baseline to the end of therapy evaluation (1‐week follow‐up visit). Results: One‐hundred and ten subjects met the inclusion and exclusion criteria and underwent a lead implant procedure. Of those, 108 had a successful procedure and 107 completed the 1‐week follow‐up visit. Ninety‐nine percent of subjects (109/110) had a motor or sensory response during needle placement (95% confidence interval [CI]: 95%–100%) and 97% of subjects (107/110) had a motor or sensory response during lead placement (95% CI: 92%–99%). The majority of subjects (88%, 95/108) reported their bladder condition was better at the follow‐up visit compared to before the PNE implant procedure, as reported in PGI‐I. Subjects reported being satisfied with how the therapy impacted their voiding symptoms (82%, 88/108) and that they would recommend this therapy (87%, 94/108) to other patients. Symptom improvement was demonstrated with urinary urge incontinence subjects having an average of 4.2 ± 3.4 urinary incontinence episodes/day at baseline and 2.2 ± 2.5 at follow‐up, and urinary frequency subjects having an average of 12.5 ± 4.4 voids/day at baseline and 10.5 ± 4.3 voids/day at follow‐up. Lead removal was deemed to be easy and safe by the implanting physician, with a total of three adverse device effects in 3/110 subjects. No event was categorized as serious and all were resolved without sequelae. Conclusions: The updated InterStim PNE lead with a more robust design and greater distensibility designed to reduce migration was shown to have a high rate of motor or sensory response during lead placement. Furthermore, subjects reported high rates of global improvements and amelioration of symptoms, and the lead was easy to remove with minimal morbidity.